2007
DOI: 10.1590/s0004-282x2007000300032
|View full text |Cite
|
Sign up to set email alerts
|

Benign monomelic amyotrophy with proximal upper limb involvement: case report

Abstract: Monomelic amyotrophy (MA) is a rare condition in which neurogenic amyotrophy is restricted to an upper or lower limb. Usually sporadic, it usually has an insidious onset with a mean evolution of 2 to 4 years following first clinical manifestations, which is, in turned, followed by stabilization. We report a case of 20-years-old man who presented slowly progressive amyotrophy associated with proximal paresis of the right upper limb, which was followed by clinical stabilization 4 years later. Eletroneuromyograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Our patient presented with an uncommon form of MA, affecting the shoulder and arm muscles instead of the commonly seen hand and forearm disease. Rare cases of proximal upper limb MA have been reported in the literature [4][5][6][7] . This patient did not have sensory symptoms or upper motor neuron signs during 2 years, or clinical or electrophysiological evidence for a widespread disease in bulbar or other limb muscles, indicating the benign nature of this condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our patient presented with an uncommon form of MA, affecting the shoulder and arm muscles instead of the commonly seen hand and forearm disease. Rare cases of proximal upper limb MA have been reported in the literature [4][5][6][7] . This patient did not have sensory symptoms or upper motor neuron signs during 2 years, or clinical or electrophysiological evidence for a widespread disease in bulbar or other limb muscles, indicating the benign nature of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is more prevalent in India, Japan, and other Asian countries, but many cases have been reported from other parts of the world as well [3][4][5] . One report from India found that MA comprises approximately 12.8% of lower motor neuron diseases 5 . MMA typically exhibits unilateral or asymmetric weakness and atrophy of the distal upper extremity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests recent disease progression in the proximal portion of the extremity. Similarly, a 23-year-old man in Brazil had monomelic amyotrophy that invaded the unilateral proximal upper extremity and tested malignant on both neurological and EMG screenings (12). In that case, progression to the proximal portion occurred in the early disease stage, unlike the present case, in which invasion into the proximal upper extremity occurred 9 years after disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…It's known that image exams can show parenchyma changes in the low cervical region. Fleeting neck, the findings become more evident with a large reduction of the dural space [8][9][10][11][12][13] . At the MRI, findings are more evident, with an important reduction of the dural space.…”
Section: Discussionmentioning
confidence: 99%